Genetic variants in IL15 associate with progression of joint destruction in rheumatoid arthritis: a multicohort study. Issue 10 (22nd March 2012) - Knevel, R; Krabben, A; Brouwer, E; Posthumus, M D; Wilson, A G; Lindqvist, E; Saxne, T; de Rooy, D; Daha, N; van der Linden, M P M; Stoeken, G; van Toorn, L; et al.
Abstract : Background: Interleukin (IL)-15 levels are increased in serum, synovium and bone marrow of patients with rheumatoid arthritis (RA). IL-15 influences both the innate and the adaptive immune response; its major role is activation and proliferation of T cells. There are also emerging data that IL-15 affects osteoclastogenesis. The authors investigated the association of genetic variants in IL15 with the rate of joint destruction in RA. Method: 1418 patients with 4885 x-ray sets of both hands and feet of four independent data sets were studied. First, explorative analyses were performed on 600 patients with early RA enrolled in the Leiden Early Arthritis Clinic. Twenty-five single-nucleotide polymorphisms (SNPs) tagging IL-15 were tested. Second, SNPs with significant associations in the explorative phase were genotyped in data sets from Groningen, Sheffield and Lund. In each data set, the relative increase of the progression rate per year in the presence of a genotype was assessed. Subsequently, data were summarised in an inverse weighting meta-analysis. Results: Five SNPs were significantly associated with rate of joint destruction in phase 1 and typed in the other data sets. Patients homozygous for rs7667746, rs7665842, rs2322182, rs6821171 and rs4371699 had respectively 0.94-, 1.04-, 1.09-, 1.09- and 1.09-fold rate of joint destruction compared to other patients (p=4.0×10 −6, p=3.8×10 −4, p=5.0×10 −3, p=5.0×10 −3 and p=9.4×10 −3 ). Discussion: Independent replication was not obtained, possibly due to insufficient power. Meta-analyses of all data sets combined resulted in significant results for four SNPs (rs7667746, p<0.001; rs7665842, p<0.001; rs4371699, p=0.01; rs6821171, p=0.01). These SNPs were also significant after correction for multiple testing. Conclusion: Genetic variants in IL-15 are associated with progression of joint destruction in RA.